2010
DOI: 10.1016/j.bpj.2010.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Spatially Regulated β-Catenin Dynamics and Invasion in Intestinal Crypts

Abstract: Experimental data (e.g., genetic lineage and cell population studies) on intestinal crypts reveal that regulatory features of crypt behavior, such as control via morphogen gradients, are remarkably well conserved among numerous organisms (e.g., from mouse and rat to human) and throughout the different regions of the small and large intestines. In this article, we construct a partial differential equation model of a single colonic crypt that describes the spatial distribution of Wnt pathway proteins along the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…One resolution of the problem is to develop coarsegrained models, which replicate the essential features of the original model, but to which established mathematical techniques such as asymptotic and bifurcation analysis may be applied. This remains an area of current research (Fozard et al, 2010;Murray et al, 2010), the key difficulty being how to retain in such coarse-grained models the necessary level of detail and spatial resolution to represent mutations in single cells.…”
Section: Discussionmentioning
confidence: 99%
“…One resolution of the problem is to develop coarsegrained models, which replicate the essential features of the original model, but to which established mathematical techniques such as asymptotic and bifurcation analysis may be applied. This remains an area of current research (Fozard et al, 2010;Murray et al, 2010), the key difficulty being how to retain in such coarse-grained models the necessary level of detail and spatial resolution to represent mutations in single cells.…”
Section: Discussionmentioning
confidence: 99%
“…So far, most studies have focused either on the impact of a gradient in the context of the signal transduction (Melen et al, 2005; Murray et al, 2010) or in the context of gene regulatory networks (Balaskas et al, 2012) but did not interlace both aspects. Our analysis showed that the differential integration of the Wnt and the APC concentration into the signaling processes has two consequences.…”
Section: Discussionmentioning
confidence: 99%
“…β-Catenin is one of the key proteins in Wnt signaling pathway [23, 27], the change of the concentration of β-Catenin have been modeled by equation (3) [30, 31]. d[βCatenin]dt=atrue(true([Wnt]+bc[Wnt]+dtrue)true(ee+[βCatenin]true)+ftrue)[βCatenin].…”
Section: Methodsmentioning
confidence: 99%